Cuba 2026 - Boobbyer, Claire; Bleszynska, Katya; Sainsbury, Brendan; Waterson, Luke, 1981- (Lonely Planet guidebooks., 2025)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Cuba. Discover Cuba's most popular experiences and best kept secrets from digging your toes into the sand at one of the country's most beautiful beaches, curving Playa Ancón; to visiting Playa Tortuga for a chance to see endangered green marine turtles; and scouting epic street art in San Isidro's Art District.